Analysis of the Suitability of Contextual Learning Materials in the Islamic Religious Education Curriculum - Roza, Mafira; Berutu, Ahnaf Istiqlal; Sari, Indah Permata (Integrasi: Jurnal Studi Islam dan Humaniora, 2025)
This study aims to analyze the suitability of contextual learning materials in the Islamic Religious Education (PAI) curriculum. The research employs a qualitative descriptive approach with document analysis techniques. Data were obtained from PAI learning materials used in secondary schools and compared with the applicable curriculum standards. The results indicate that most learning materials have integrated students’ real-life context; however, some content still needs to be adjusted to be more relevant and applicable. These findings are expected to serve as a reference for teachers and curriculum developers in improving the quality of contextual PAI learning materials.